Pelatihan Membaca Dengan Menggunakan Media Papan Pintar Di Desa Pangkalan - Husniah Husniah; Dede Nurannisa; Dede Imtihanudin; Ratna Dewi; Adel Farid Hasyim (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2023)
The purpose of this training is to introduce learning media to Pangkalan Village students. Creating fun reading learning media for children. We have skills in designing Smart Board learning media as reading learning media for elementary school children. The subject of this training is for grade 1 elementary school children in Pangkalan village. Implementation of training is an initial survey to record training participants, arrange permits to carry out training. The method used is direct practice. The direct practice method is used by the trainees so that students are able to read using the smart board media.